PENERAPAN LATIHAN DEKODING PERSEPSI AUDITORI UNTUK MENSTIMULASI RESPON TERHADAP BUNYI PADA KLIEN DISAUDIA BILATERAL PROFOUND: Application of Auditory Perception Decoding Exercises to Stimulate Responses to Sound in Bilateral Profound Dysaudia Clients - Ami Rachmi; Yosrika Yosrika (JURNAL TERAS KESEHATAN, 2021)
The communication process will occur if there are at least two people exchanging information through the codes conveyed by the speaker and also the codes understood by the listener. Meanwhile, dysaudia is a speech impediment that is directly related to hearing impairment resulted in the inability of the sufferer to communicate well verbally. This study aims to determine the implementation and success rate of auditory perception decoding exercises to improve response to sound on a Bilateral Profound Disaudia client. This research used a single-subject experiment. Data were collected through techniques of interview to the client's parents, direct observation of the client, and study of the client's medical record document. The collected data were then analyzed to draw conclusions. Results of the study showed that after 20 meetings of therapy using the Decoding Exercise method, the ability of the client response toward sound increased from 0 in the initial test to 3 in the final test with a success percentage of 37.5%. Based on the results, it can be concluded that the application of decoding exercises to improve the response to sound on the profound bilateral dysaudia client is quite successful.